Analisis Bentuk dan Makna Tindak Tutur Tidak Langsung dalam Film Pendek “Tiflun Ta’arrada li al-Tanamur li Annahu Ghabi Asbaha ‘Abqariyya” - Ahyia, Dwian Saktiawati; Khusniyati, Itsna; Hamzah, Andi Abdul; Pallawagau, Baso (Al-Fashahah: Journal of Arabic Education, Linguistics, and Literature, 2025)
This study aims to reveal the forms and meanings of indirect speech acts in an Arabic short film titled “Tiflun Ta'arrada li al-Tanamur li annahu Ghabi Asbaha 'Abqariyya”. The research method used is a qualitative approach with descriptive analysis. The data in this study consisted of words, phrases, and sentences that reflected indirect speech acts. The data were analyzed using content analysis and presented in the form of a description. The results of the analysis show that in the short film “Tiflun Ta'arrada li al-Tanamur li annahu Ghabi Asbaha 'Abqariyya” there are 17 indirect speech acts with 3 forms, namely assertive, directive, and expressive. Indirect speech acts provide an overview of how a speech act has various meanings, intentions, and purposes according to the context in which it is uttered. This analysis is expected to provide new insights into the dynamics of communication in the context of Arab culture and demonstrate the importance of indirect speech acts as a tool for maintaining politeness. Through this research, it is hoped that readers can gain a deeper understanding of the complexity of communication in films and the pragmatic values contained therein.